The Effect of Entrepreneurial Knowledge, Entrepreneurial Competence, and Innovation Capability on Business Achievement, with Business Capability as an Intervening Variable - LIzfa Karina; M. Arifiyanto (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the factors influencing business achievement among entrepreneurs through the role of business capability. The object of this research focuses on business actors who face challenges in improving business performance and sustainability amid increasingly competitive market conditions. The main problem addressed in this study is how entrepreneurial knowledge, entrepreneurial competence, and innovation capability influence business capability and ultimately impact business achievement. Therefore, this study aims to analyze the effect of these variables on business achievement with business capability acting as an intervening variable. This research employs a quantitative approach, with data collected through questionnaires distributed to business actors as respondents. The collected data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) version 4.1.1.6 approach to examine the relationships among variables in the research model. The results show that entrepreneurial knowledge, entrepreneurial competence, and innovation capability have a positive influence on business capability, which in turn contributes to improving business achievement. These findings indicate that improving entrepreneurs’ knowledge, skills, and innovation capabilities can strengthen their ability to manage resources and business strategies effectively, thereby enhancing overall business performance. In conclusion, the development of entrepreneurial capacity and innovation capability plays a crucial role in supporting the success and achievement of business performance.